2019
DOI: 10.1093/infdis/jiz547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Universal Antiretroviral Treatment Eligibility on Rapid Treatment Initiation Among Young Adolescents with Human Immunodeficiency Virus in Sub-Saharan Africa

Abstract: Background Young adolescents with perinatally-acquired HIV are at risk for poor care outcomes. We examined whether universal antiretroviral treatment (ART) eligibility policies (Treat All) improved rapid ART initiation following care enrollment among 10-14-year-olds in seven sub-Saharan African countries. Methods Regression discontinuity analysis and data for 6,912 10-14-year-old patients were used to estimate changes in rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
8
0
4
Order By: Relevance
“…Increases in rapid ART initiation observed after the implementation of a treat all policy in this current study are similar to a report from sub‐Saharan Africa, where a treat all policy adoption also increased the numbers of young adolescents accessing ART rapidly [4, 10]. Policy changes regarding rapid ART initiation led to decreased mortality rates and increased retention in care, similar to those in our study [29, 30].…”
Section: Discussionsupporting
confidence: 90%
“…Increases in rapid ART initiation observed after the implementation of a treat all policy in this current study are similar to a report from sub‐Saharan Africa, where a treat all policy adoption also increased the numbers of young adolescents accessing ART rapidly [4, 10]. Policy changes regarding rapid ART initiation led to decreased mortality rates and increased retention in care, similar to those in our study [29, 30].…”
Section: Discussionsupporting
confidence: 90%
“…In 2018, 35% of participants entering HIV care were prescribed ART the same day 14 . Many reports from cohorts, clinic-based or program-based sites have published trends of shorter times to ART initiation in more recent years 13 , 15 22 particularly after 2015 when “treat all” policy was introduced by WHO 6 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies on whether HIV "Treat All" has improved ART initiation among adolescents are inconclusive. Positive effects have been shown in some studies, while others have shown that they are still at risk of not initiating ART [23,[27][28][29]. To our knowledge, no evidence-based strategies are currently being implemented in Zimbabwe on a broader scale under "Treat All" to promote ART initiation among adolescents and young adults.…”
Section: Plos Onementioning
confidence: 99%